Efficacy of vaccination and previous infection against the Omicron BA.1 variant in Syrian hamsters - Halfmann, Peter J.; Kuroda, Makoto; Maemura, Tadashi; Chiba, Shiho; Armbrust, Tammy; Wright, Ryan; Balaram, Ariane; Florek, Kelsey R.; Bateman, Allen C.; Kawaoka, Yoshihiro (Cell reports (Cambridge), 2022)
The emergence of the SARS-CoV-2 Omicron (B.1.1.529) variant with a surprising number of spike mutations raises concerns about reduced sensitivity of this virus to antibody neutralization and subsequent vaccine breakthrough infections. Here, we infect Moderna mRNA-vaccinated or previously infected hamsters with the Omicron BA.1 variant. While the Moderna mRNA vaccine reduces viral loads in the respiratory tissues upon challenge with an early S-614G isolate, the vaccine efficacy is not as pronounced after infection with the Omicron variant. Previous infection with the early SARS-CoV-2 isolate prevents replication after rechallenge with either virus in the lungs of previously infected hamsters, but the Omicron variant replicates efficiently in nasal turbinate tissue. These results experimentally demonstrate in an animal model that the antigenic changes in the Omicron variant are responsible for vaccine breakthrough and re-infection. [Display omitted] •Moderna-vaccinated hamsters are more susceptible to BA.1 than to an early isolate•BA.1 replicates less efficiently than an early isolate in the lungs of hamsters•Prior infection does not prevent BA.1 replication in the nasal turbinates of hamsters•Prior infection does prevent BA.1 replication in the lungs of hamsters Halfmann et al. report that while the Moderna mRNA vaccine reduces BA.1 replication in vaccinated hamsters, the vaccine efficacy is not as pronounced as that against an early prototypical SARS-CoV-2 isolate. Previously infected hamsters are better protected than vaccinated hamsters against re-infection with the BA.1 variant.